A preliminary survey of flowering medicinal plants found in Bario Nanga, Guimbal, Iloilo. - Prieto, Lourfame Decolongon
A survey on flowering medicinal plants was conducted in Barrio Nanga, Guimbal, on the basis that about eighty percent of the population still depend on folk medicine and herbals in the treatment of their common ailments., A total of thirty-four pplants were recommended by the herbolarios as having medicinal and specific curative properties. These were represented by twenty families namely: Bromeliaceae and Palmae under Class Monocotyledoneae; Acanthaceae, Anacardiaceae, Annonaceae, Apocynaceae, Caricaceae, Combretaceae, Compositae, Euphorbiaceae, Leguminosae, Malvaceae, Meliaceae, Moringaceae, Myrtaceae, Oleaceae, Portulacaceae, Rubiaceae, Sapotaceae and Solanaceae under Class Dicotyledoneae. Among these families, Family Apocynaceae represents a majority of the plants surveyed.